(untitled) (The Southeast Asian Journal of Tropical Medicine and Public Health, 2021)
Worldwide, tuberculosis (TB) is one of the top ten causes of death. Molecular epidemiology has contributed significantly to understanding of TB transmission. One of the most significant methods is variable number tandem repeat (VNTR) typing, which determines variations of tandem repeat copy numbers, but the method is laborious. A MinION nanopore sequencer was applied to determine copy numbers of mycobacterial interspersed repetitive unit (MIRU)-VNTR loci of Mycobacterium tuberculosis isolates, which eases workload by barcode-multiplexing and analyzing 276 amplicons in a single experiment, and also enables detection of single nucleotide variants (SNVs). MIRU-VNTR loci (n = 24) were PCR amplified and amplicons, confirmed by agarose gel-electrophoresis, were pooled prior to nanopore nucleotide sequencing library preparation. Probabilities of correctly assigned genotypes were calculated using a four-parameter logistic regression model. Unambiguous genotypes were obtained from 245 (89%) amplicons and 14 putative SNV sites were detected distributed among eleven VNTR loci. In conclusion, long-read sequencing allowed uncomplicated genotyping of minisatellites of M. tuberculosis isolates from chronic pulmonary TB patients and confirmed the presence of SNVs within MIRU-VNTR loci.